Dual-Energy Computed Tomography Gemstone Spectral Imaging: A Novel Technique to Determine Human Cardiac Calculus Composition. Issue 2 (March 2016) - Cheng, Ching-Li; Chang, Hsiao-Huang; Ko, Shih-Chi; Huang, Pei-Jung; Lin, Shan-Yang
Abstract : Objective: Understanding the chemical composition of any calculus in different human organs is essential for choosing the best treatment strategy for patients. The purpose of this study was to assess the capability of determining the chemical composition of a human cardiac calculus using gemstone spectral imaging (GSI) mode on a single-source dual-energy computed tomography (DECT) in vitro. Methods: The cardiac calculus was directly scanned on the Discovery CT750 HD FREEdom Edition using GSI mode, in vitro. A portable fiber-optic Raman spectroscopy was also applied to verify the quantitative accuracy of the DECT measurements. Results: The results of spectral DECT measurements indicate that effective Z values in 3 designated positions located in this calculus were 15.02 to 15.47, which are close to values of 15.74 to 15.86, corresponding to the effective Z values of calcium apatite and hydroxyapatite. The Raman spectral data were also reflected by the predominant Raman peak at 960 cm −1 for hydroxyapatite and the minor peak at 875 cm −1 for calcium apatite. Conclusions: A potential single-source DECT with GSI mode was first used to examine the morphological characteristics and chemical compositions of a giant human cardiac calculus, in vitro. The CT results were consistent with the Raman spectral data, suggesting that spectral CT imaging techniques could be accurately used to diagnose and characterize the compositional materials in the cardiac calculus.